2014
DOI: 10.3762/bjoc.10.300
|View full text |Cite
|
Sign up to set email alerts
|

A study on the inhibitory mechanism for cholesterol absorption by α-cyclodextrin administration

Abstract: Summary Background: Micelle formation of cholesterol with lecithin and bile salts is a key process for intestinal absorption of lipids. Some dietary fibers commonly used to reduce the lipid content in the body are thought to inhibit lipid absorption by binding to bile salts and decreasing the lipid solubility. Amongst these, α-cyclodextrin (α-CD) is reportedly one of the most powerful dietary fibers for decreasing blood cholesterol. However, it is difficult to believe that α-CD directly removes cholesterol bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…CDs are cyclic oligosaccharides consisting of six (αCD), seven (βCD), or eight (γCD) α-1,4-linked glycopyranose units, with a hydrophilic hydroxyl group on their outer surface and a hydrophobic cavity in their centre. In these CDs, αCD is widely used as a water-soluble dietary fibre 8 . Addition of 1.5% αCD to mice has been shown to decrease the numbers of caecal bacteria belonging to the genus Clostridium 9 .…”
Section: Introductionmentioning
confidence: 99%
“…CDs are cyclic oligosaccharides consisting of six (αCD), seven (βCD), or eight (γCD) α-1,4-linked glycopyranose units, with a hydrophilic hydroxyl group on their outer surface and a hydrophobic cavity in their centre. In these CDs, αCD is widely used as a water-soluble dietary fibre 8 . Addition of 1.5% αCD to mice has been shown to decrease the numbers of caecal bacteria belonging to the genus Clostridium 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of its interaction with lecithin precipitation, aCD decreased the micellar cholesterol solubility of dietary fat in intestinal fluid and prevented the absorption of cholesterol in the small intestine. (13,37,38) We expected that aCD would exert similar effects in this study. However, aCD did not alter HFD-induced increase in body weights and epididymal fat weight in our study.…”
Section: Discussionmentioning
confidence: 67%
“…It has been shown that both bile salts and phospholipids can act as guest molecules in CD complexes. [216][217][218] As mentioned earlier in this review, in multicomponent systems, competition between different guest molecules may result in reorganization of complexes and in dynamic systems, such as the intestinal environment, complex composition (and, consequently, CD aggregation) can change over time. As a result, the aggregation behavior and overall performance of the formulation in biorelevant media and in pure water may strongly differ.…”
Section: Challenges and Opportunitiesmentioning
confidence: 84%